Attractiveness of tourist destinations and collaborative tourism governance on Revisit Intention as a support for the tourism economy of the Paropo area of Dairi Regency with Tourist Experience as an Intervening Variable - Daulay, Zulia Rifda; Pasaribu, Deby Siska Oktavia; Martin, Martin (Jurnal Multidisiplin Teknologi dan Arsitektur, 2024)
The challenge of tourism is how to create tourists who are loyal to tourist destinations because every corner of tourism has an impact on the economy for the business community in the tourist destination area, if tourist visitors enjoy their tour and have the intention to return to visit the tour, it will have an impact on increasing the economy of the community located in tourist destinations. This research will be conducted in Sumatra Utaran precisely at the location of the paropo tourist spot in Dairi Regency with a population of paropo tourist visitors who have visited at least twice as many as 230 tourists, this research approach is quantitative with the Structural Equation Modeling (SEM) model. This approach is able to test a model that is most ideal in estimating endogenous variables, the sampling technique in this study uses Non-probability sampling where sampling does not provide opportunities or opportunities for each element or member to be selected as a sample The analysis model used to test the hypothesis in this study is multiple regression analysis using the Smart PLS application Directly that the attractiveness of tourist destinations, collaborative tourism governance and tourist experience have a significant effect on Revisit Intention as a support for the tourism economy of the Paropo area of Dairi Regency. Directly that the attractiveness of tourist destinations and collaborative tourism governance have a significant effect on tourist experience as a support for the tourism economy of the Paropo area of Dairi Regency. Indirectly, tourist experience has a significant role in mediating the attractiveness of tourist destinations and collaborative tourism governance on revisit intension as a support for the tourism economy of the Paropo area of Dairi Regency